Women Mobilizing for Change: Resisting State Violence from Repressive Drug Policies. (June 2022) - Birgin, Ruth; Fernández, Adrià Cots; Nougier, Marie; Youngers, Coletta
Punitive drug laws have had a differentiated and violent impact on women. State-driven stigma, criminalization, and abuse act as major barriers between women who use drugs and critical services, driving disproportionate health and safety harms. At the same time, women involved in illegal drug activities suffer the brunt of disproportionate drug laws, which exacerbate poverty and intersecting forms of discrimination, and have increased dramatically the global number of women behind bars. Although UN fora and women's rights organizations have paid little attention to their situation, affected women have mobilized to affirm their rights and vindicate their experiences, including at CSW65. From grassroots campaigns to organizations of formerly incarcerated women or peer-led harm reduction programs, women have stepped in to provide the support that States have failed to deliver. Decriminalization, reforms of draconian drug laws, gender-sensitive harm reduction services, and peer-led initiatives are essential to tackle violence against women.